Students’ Use of Simple Present Tense in their Descriptive Writing: An Error Analysis - Putri Nur Hafizhoh; Winny Agustia Riznanda; Hariana Amalia (Journal of English Language Learning, 2025)
This study investigated the types of errors made by the seventh-grade students at SMP N 26 Palembang on the use of the Simple Present Tense on descriptive writing, and determined the most dominant type of errors. Employing a descriptive quantitative research design, the research involved a writing task completed by 35 students. To analyze the data, the surface strategy taxonomy proposed by Dulay et al. (1982) was applied. The analysis revealed that misformation errors were the most prevalent, constituting 55.75% of total errors, followed by omission errors at 28.31%, addition errors at 9.73%, and misordering errors at 6.19%. These findings indicated significant challenges faced by the students in grasping grammatical structures, particularly in verb forms and sentence construction. The study underscored the necessity for targeted instructional strategies to address these common errors, suggesting that enhanced grammar teaching could lead to improve writing skills. The insights gained from this research serve as a valuable resource for educators aiming to refine their teaching methods and help the students achieve a better understanding of the Simple Present Tense in English writing